2006
DOI: 10.1111/j.1556-4029.2006.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Laser Microdissection Separation of Pure Spermatozoa from Epithelial Cells for Short Tandem Repeat Analysis*

Abstract: Short tandem repeat (STR) analysis is a valuable tool in identifying the source of biological stains, particularly from the investigation of sexual assault crimes. Difficulties in analysis arise primarily in the interpretation of mixed genotypes when cell separation of the sexual assailant's sperm from the victim's cells is incomplete. The forensic community continues to seek improvements in cell separation methods from mixtures for DNA typing. The feasibility of applying laser microdissection (LMD) technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 25 publications
0
54
0
1
Order By: Relevance
“…The different cell types can be recognized by morphological characteristics, various chemical staining or fluorescence labeling techniques. These methods allow to establish a clear DNA profile from few cells present in a mixture samples that otherwise had not be detected while swabbed by the major component and not detectable in the profile ( Elliott et al, 2003;Anslinger et al, 2005;Anoruo et al, 2007 ;Sanders et al, 2006). With laser micro dissection techniques ( Anslinger et al, 2007;Vandewoestyne et al, 2009), it has been shown that cells derived from a male contributor can be analyzed separately from those derived from a female contributor after morphological or fluorescent labeling identification.…”
Section: Collecting Methodologiesmentioning
confidence: 99%
“…The different cell types can be recognized by morphological characteristics, various chemical staining or fluorescence labeling techniques. These methods allow to establish a clear DNA profile from few cells present in a mixture samples that otherwise had not be detected while swabbed by the major component and not detectable in the profile ( Elliott et al, 2003;Anslinger et al, 2005;Anoruo et al, 2007 ;Sanders et al, 2006). With laser micro dissection techniques ( Anslinger et al, 2007;Vandewoestyne et al, 2009), it has been shown that cells derived from a male contributor can be analyzed separately from those derived from a female contributor after morphological or fluorescent labeling identification.…”
Section: Collecting Methodologiesmentioning
confidence: 99%
“…However, it has been reported that this cell separation process results in losses of 60–90% of the male DNA 10, 11, 12, 13. Although there have been multiple attempts for alternative methods to differentially extract sperm using acoustic trapping,14 antibody‐based capture,15 laser microdissection,16, 17, 18 nuclease‐based approaches,19 and magnetic bead‐based separation,20, 21 these methods have not been broadly available in practical applications due to the complexity and low separation yield for sperm. As a result, they are not widely in use in the community.…”
Section: Introductionmentioning
confidence: 99%
“…The use of laser capture microdissection (LCM) has been evaluated for the isolation of spermatozoa from microscope slides containing both spermatozoa and vaginal cells [4][5][6]. Elliot et al showed that LCM outperforms differential extraction for the recovery of DNA from sperm cells, especially in cases where only a few sperm cells are present [7].…”
Section: Introductionmentioning
confidence: 99%
“…Standard methods to identify spermatozoa are based on non-specific staining techniques such as hematoxylin/eosin (HE) and nuclear fast red/ picroindigocarmine (CTS or "Christmas tree stain") [10], which rely on sperm morphology for identification [4] and cannot be used for automated sperm detection. Moreover HE staining reduces the yield of DNA [4,5,11] and CTS staining results in DNA damage, probably due to the picric acid component [4].…”
Section: Introductionmentioning
confidence: 99%